Lymphocyte to monocyte ratio and serum albumin changes predict tacrolimus therapy outcomes in patients with ulcerative colitis - Natsuki Ishida; Shinya Tani; Yusuke Asai; Takahiro Miyazu; Satoshi Tamura; Mihoko Yamade; Moriya Iwaizumi; Yasushi Hamaya; Satoshi Osawa; Takahisa Furuta; Ken Sugimoto (Scientific Reports, 2022)
Abstract Tacrolimus therapy for ulcerative colitis is ineffective in certain patients; these patients require biologics or colectomy. We examined the ability of serum albumin levels and leukocyte subtypes to predict the therapeutic efficacy of tacrolimus. Patients with ulcerative colitis treated with tacrolimus were divided into non-failure and failure (required colectomy or switch to biologics or systemic steroids) groups. Serum albumin levels and leukocyte subtypes at induction, week 1, and week 2 after reaching high trough levels were retrospectively examined. Tacrolimus therapy failed in 18/45 patients within 3 months. The week 2/week 1 albumin ratio was significantly different between the failure and non-failure groups (P < 0.001). The receiver operating characteristic curve analysis revealed optimal cut-off value of the week 2/week 1 albumin ratio was 1.06, and area under the curve was 0.815. Analysis of leukocyte subtypes revealed significant between-group difference in the week 1 lymphocyte to monocyte ratio (P < 0.001). Multivariate analysis showed week 2/week 1 albumin ratio ≤ 1.06 and week 1 lymphocyte to monocyte ratio ≤ 3.86. Therefore, a low week 2/week 1 albumin and low week 1 lymphocyte to monocyte ratio predicted failure within 3 months of tacrolimus induction; a combination of these markers could accurately predict failure.